2019
DOI: 10.1089/mdr.2018.0232
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureusInfecting and Colonizing Experimental Animals, Macaques, in a Research Animal Facility

Abstract: An outbreak of methicillin-resistant Staphylococcus aureus (MRSA) infections on the skin and soft tissues of experimental macaques in the vivarium of The Rockefeller University, New York, triggered this observational and interventional study. We screened 14 macaques in the colony (samples from head, nares, and rectum) and their housing (40 environmental surfaces) four times in 1 year, for S. aureus colonization or contamination, while implementing enhanced decolonization and decontamination procedures. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Human-to-primate transmission was suggested in a study of wild primates MRSA in Nepal [63] and primates in Gabon [70]. The reverse was suggested by examination of an ST3268 strain found in macaques in primate research facilities in Singapore [68] and the United States [66,67]; this molecular type was also found in macaques in a New York research facility [65], suggesting the need for screening of animals prior to export/import. While most reports suggest preponderance of primate-associated strains, testing in a Texas facility found that their animals were colonized primarily with USA300/ST8 strains, which are common in humans and suggestive of human-to-animal transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Human-to-primate transmission was suggested in a study of wild primates MRSA in Nepal [63] and primates in Gabon [70]. The reverse was suggested by examination of an ST3268 strain found in macaques in primate research facilities in Singapore [68] and the United States [66,67]; this molecular type was also found in macaques in a New York research facility [65], suggesting the need for screening of animals prior to export/import. While most reports suggest preponderance of primate-associated strains, testing in a Texas facility found that their animals were colonized primarily with USA300/ST8 strains, which are common in humans and suggestive of human-to-animal transmission.…”
Section: Discussionmentioning
confidence: 99%